Satellitome landscape analysis of Megaleporinus macrocephalus (Teleostei, Anostomidae) reveals intense accumulation of satellite sequences on the heteromorphic sex chromosome - Utsunomia, Ricardo [UNESP]; Silva, Duílio Mazzoni Zerbinato de Andrade [UNESP]; Ruiz-Ruano, Francisco J.; Goes, Caio Augusto Gomes [UNESP]; Melo, Silvana [UNESP]; Ramos, Lucas Peres [UNESP]; Oliveira, Claudio [UNESP]; Porto-Foresti, Fábio [UNESP]; Foresti, Fausto [UNESP]; Hashimoto, Diogo Teruo [UNESP] (Springer Nature, 2019)
The accumulation of repetitive DNA sequences on the sex-limited W or Y chromosomes is a well-known process that is likely triggered by the suppression of recombination between the sex chromosomes, which leads to major differences in their sizes and genetic content. Here, we report an analysis conducted on the satellitome of Megaleporinus macrocephalus that focuses specifically on the satDNAs that have been shown to have higher abundances in females and are putatively located on the W chromosome in this species. We characterized 164 satellite families in M. macrocephalus, which is, by far, the most satellite-rich species discovered to date. Subsequently, we mapped 30 satellites, 22 of which were located on the W chromosome, and 14 were shown to exist only on the W chromosome. Finally, we report two simple, quick and reliable methods that can be used for sex identification in M. macrocephalus individuals using fin clips or scales, which could be applicable to future studies conducted in the field of aquaculture.